Article IV of the Fund's Articles of Agreement : An Overview of the Legal Framework. (Policy Papers; Policy Paper ;, 2006)
This paper is designed to assist the Executive Board in its consideration of the steps that could be taken to provide members with more specific guidance as to their obligations under Article IV.